2006
DOI: 10.1002/app.23528
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of bovine serum albumin using MPEG–PCL diblock copolymers as implantable protein carriers

Abstract: MPEG-PCL diblock copolymers consisting of methoxy polyethylene glycol (MPEG) and poly(-caprolactone) (PCL) as drug carriers were synthesized by ringopening polymerization. It is possible to control the balance between hydrophilic and hydrophobic by changing the MPEG and the ratio of -CL to MPEG. Implantable wafers were easily fabricated by the direct compression method after physical mixing of diblock copolymers and bovine serum albumin-fluorescein isothiocyanate (BSA-FITC) as a model protein drug. The BSA rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Several other thermosensitive copolymers of PEG with aliphatic polyesters were synthesized and applied for drug delivery. Some examples are AB, ABA, and BAB copolymers of PEG with caprolactone (PCL) and δ-valerolactone (PVL). The in vitro and in vivo release of fluorescein isothiocyanate-labeled bovine serum albumin (BSA–FITC) was studied from PEG–PCL diblock copolymers gels and compared to that of Pluronic gels, and the studies demonstrated longer in vivo stability of PEG–PCL hydrogels and enhanced capability to provide sustained protein release over 10 days, as compared to Pluronic gels, where destabilization and drug release within 3 days was observed. , …”
Section: Smart Hydrogelsmentioning
confidence: 99%
“…Several other thermosensitive copolymers of PEG with aliphatic polyesters were synthesized and applied for drug delivery. Some examples are AB, ABA, and BAB copolymers of PEG with caprolactone (PCL) and δ-valerolactone (PVL). The in vitro and in vivo release of fluorescein isothiocyanate-labeled bovine serum albumin (BSA–FITC) was studied from PEG–PCL diblock copolymers gels and compared to that of Pluronic gels, and the studies demonstrated longer in vivo stability of PEG–PCL hydrogels and enhanced capability to provide sustained protein release over 10 days, as compared to Pluronic gels, where destabilization and drug release within 3 days was observed. , …”
Section: Smart Hydrogelsmentioning
confidence: 99%
“…Improving and/or tailoring the properties of PCL commonly involve copolymerization of ε‐caprolactone with other suitable monomers. Hydrophilic segments such as poly(ethylene glycol) (PEG), methoxy poly(ethylene glycol) (MPEG) or poly(ethylene oxide)‐poly(propylene oxide)‐poly(ethylene oxide) (PEO‐PPO‐PEO) have been introduced into PCL chain to change the hydrophobicity and improve the biodegradability characteristic of PCL 11–13. Hydrophobic segments such as polylactide (PLA) or polyglycolide (PGA) have also been introduced into PCL chain to reduce its isotacticity so as to lower its crystallinity which is closely related to degradation/erosion rate 14.…”
Section: Introductionmentioning
confidence: 99%
“…And the presences of heat, moist and acidic environment would accelerate the degradation of polymers. in mPEG segment which resulted in improved water-penetration into the system [146].…”
Section: Storage Conditionsmentioning
confidence: 99%